2017
DOI: 10.1002/2017jd027139
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Variability and Anomalies Observed During SENEX and SEAC4RS Campaigns in 2013

Abstract: Tropospheric ozone variability occurs because of multiple forcing factors including surface emission of ozone precursors, stratosphere‐to‐troposphere transport (STT), and meteorological conditions. Analyses of ozonesonde observations made in Huntsville, AL, during the peak ozone season (May to September) in 2013 indicate that ozone in the planetary boundary layer was significantly lower than the climatological average, especially in July and August when the Southeastern United States (SEUS) experienced unusual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 106 publications
(149 reference statements)
3
11
1
Order By: Relevance
“…It is consistent with the O 3 -RH correlation that transitioning from positive to negative south of 37 • N [39]. The O 3 /RH regression slopes in Huntsville, AL, during the peak O 3 season (May to September) in 2013 were −1.0, −0.6, −0.5, and −3.6 ppb/% for the surface, PBL, mid-troposphere, and upper troposphere, respectively [41]. O 3 anomalies (deviation from normal value) reached +12 ppb from 30 to 36 • N in 1999, and 4-7 ppb higher, during the historic 2007 drought in the Southeastern United States (U.S.) [39,42].…”
Section: O 3 Sensitivity To Meteorologysupporting
confidence: 68%
See 1 more Smart Citation
“…It is consistent with the O 3 -RH correlation that transitioning from positive to negative south of 37 • N [39]. The O 3 /RH regression slopes in Huntsville, AL, during the peak O 3 season (May to September) in 2013 were −1.0, −0.6, −0.5, and −3.6 ppb/% for the surface, PBL, mid-troposphere, and upper troposphere, respectively [41]. O 3 anomalies (deviation from normal value) reached +12 ppb from 30 to 36 • N in 1999, and 4-7 ppb higher, during the historic 2007 drought in the Southeastern United States (U.S.) [39,42].…”
Section: O 3 Sensitivity To Meteorologysupporting
confidence: 68%
“…O 3 was at first removed efficiently by chemical reactions then increased rapidly when warmer and O 3 -richer air from aloft was mixed downward to the surface. Leibensperger et al [6] reported that the frequency of summertime mid-latitude cyclones (and their associated cold fronts) tracking across eastern North America at [40][41][42][43][44][45][46][47][48][49][50] • N is a strong predictor of stagnation and O 3 pollution days in the eastern US.…”
Section: Introductionmentioning
confidence: 99%
“…Within the free troposphere from 2 to 6 km, median and lower quartile O 3 values were from 73 to 81 and 66 to 74 ppbv, respectively. This is markedly larger than the 50-65 ppbv baseline O 3 estimates derived for Trinidad Head, CA; Boulder, CO; and Huntsville, AL, USA (Stauffer et al, 2016;Kuang et al, 2017). This highlights the infrequency (i.e., < 25 % of the time) of measuring less than 66 ppbv of O 3 within the boundary layer and free troposphere and the subsequent regulatory challenge of meeting the 8 h Korean O 3 standard (60 ppbv).…”
Section: Ozonesonde Profiles At Trfmentioning
confidence: 83%
“…The results obtained from the sondes have been rather controversial which seems to be the consequence of the individual data-filtering approach. Recent sonde studies confirm a rather high percentage of STT: At the same latitude as Table Mountain, but in the south-eastern United States, ozone-sonde measurements at Huntsville (Alabama, U.S.A., 35º N) were analysed between May and September 2013 (Kuang et al, 2017). There, the summer minimum was 23 % (August), and 50-60 % were reached in May-20 June.…”
Section: Discussionmentioning
confidence: 93%
“…STT analyses have also been derived from ozone-sonde data (e.g., Beekmann et al, 1997;Colette and Ancellet, 2005;Kuang et al, 2017;Tarasick et al, 2019). Ozone sondes yield a substantially lower temporal data coverage than lidar sounding.…”
Section: Discussionmentioning
confidence: 99%